2016
DOI: 10.3390/min6030068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Grinding Time on Gold Dissolution in Cyanide Solution

Abstract: Abstract:The recovery of gold by ore leaching is influenced by the size of the particles and the chemical environment. The effect of particle size on the dissolution of gold is usually studied using mono-size particles as the gold in solution comes from the ore of a unique leached particle size. This paper proposes a method to estimate the gold dissolution as a function of particle size using a bulk ore sample, i.e., with the dissolved gold coming from the various sizes of particles carried by the ore. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…For example, in the flotation process, it has been found that extremely fine particles (e.g., <20 µm) have lower collision efficiency with bubbles and this results in losses of valuable minerals [42]. In addition, regarding the leaching process, although finely ground raw material with large surface area is usually required for efficient extraction of valuable metals, recent research studies indicate that for certain ores there is a specific size fraction for which a maximum leaching rate is observed [43,44]. In this context, the AR method may be used to determine the optimal parameters of the grinding process, i.e., residence time, media/feed size, and media filling ratio, which maximize the desired size range of grinding products [23,[44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the flotation process, it has been found that extremely fine particles (e.g., <20 µm) have lower collision efficiency with bubbles and this results in losses of valuable minerals [42]. In addition, regarding the leaching process, although finely ground raw material with large surface area is usually required for efficient extraction of valuable metals, recent research studies indicate that for certain ores there is a specific size fraction for which a maximum leaching rate is observed [43,44]. In this context, the AR method may be used to determine the optimal parameters of the grinding process, i.e., residence time, media/feed size, and media filling ratio, which maximize the desired size range of grinding products [23,[44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…In previous decades, the extraction of gold was performed from gold ores by using cyanide leaching [42,43]. Due to the environmental issues of cyanide, of halides, aqua regia, thiosulfate and thiourea are now used as alternative materials [44].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous applications to flotation processes (Trahar, 1981;Bazin and Proulx, 2000) and hydrocyclones (Laplante and Finch, 1984) operation are found in the literature. Some results are also found for gold leaching (Egan et al, 2013) and hydraulic classification (Bazin et al, 2012). However few papers were found to describe the operation of spirals in terms of partition curves (Atasoy and Spottiswood, 1995;Holland-Batt and Holtham, 1991;Richards et al, 2000).…”
Section: Introductionmentioning
confidence: 89%